All-Covalent Organic Framework Nanofilms Assembled Lithium-Ion Capacitor to Solve the Imbalanced Charge Storage Kinetics - Xu, Xiaoyang; Zhang, Jia; Zhang, Zihao; Lu, Guandan; Cao, Wei; Wang, Ning; Xia, Yunmeng; Feng, Qingliang; Qiao, Shanlin (Nano-Micro Letters, 2024)
Free-standing covalent organic framework (COFs) nanofilms exhibit a remarkable ability to rapidly intercalate/de-intercalate Li+ in lithium-ion batteries, while simultaneously exposing affluent active sites in supercapacitors. The development of these nanofilms offers a promising solution to address the persistent challenge of imbalanced charge storage kinetics between battery-type anode and capacitor-type cathode in lithium-ion capacitors (LICs). Herein, for the first time, custom-made COFBTMB-TP and COFTAPB-BPY nanofilms are synthesized as the anode and cathode, respectively, for an all-COF nanofilm-structured LIC. The COFBTMB-TP nanofilm with strong electronegative–CF3 groups enables tuning the partial electron cloud density for Li+ migration to ensure the rapid anode kinetic process. The thickness-regulated cathodic COFTAPB-BPY nanofilm can fit the anodic COF nanofilm in the capacity. Due to the aligned 1D channel, 2D aromatic skeleton and accessible active sites of COF nanofilms, the whole COFTAPB-BPY//COFBTMB-TP LIC demonstrates a high energy density of 318 mWh cm−3 at a high-power density of 6 W cm−3, excellent rate capability, good cycle stability with the capacity retention rate of 77% after 5000-cycle. The COFTAPB-BPY//COFBTMB-TP LIC represents a new benchmark for currently reported film-type LICs and even film-type supercapacitors. After being comprehensively explored via ex situ XPS, 7Li solid-state NMR analyses, and DFT calculation, it is found that the COFBTMB-TP nanofilm facilitates the reversible conversion of semi-ionic to ionic C–F bonds during lithium storage. COFBTMB-TP exhibits a strong interaction with Li+ due to the C–F, C=O, and C–N bonds, facilitating Li+ desolation and absorption from the electrolyte. This work addresses the challenge of imbalanced charge storage kinetics and capacity between the anode and cathode and also pave the way for future miniaturized and wearable LIC devices. Highlights: 1 An all-covalent organic framework (COF) nanofilm-structured lithium-ion capacitor (LIC) was developed by custom-made COF nanofilms as the anode/cathode. 2 The COF nanofilm-structured LIC exhibits good electrochemical properties via the fast Li+ transport kinetics of the anodic COFBTMB-TP nanofilm and the high specific capacity of the cathodic COFTAPB-BPY nanofilm. 3 This work can realize the charge storage kinetics and capacity balance of anode/cathode in COFTAPB-BPY//COFBTMB-TP LIC.